Perspektif Hukum Islam Terhadap Praktik Jual Beli Kayu Sengon Dengan Perjanjian Penundaan Penebangan Dalam Jangka Waktu Tertentu - Fawaid Fawaid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
the types of buying and selling transactions and their implementation continue to change and certain types have become a habit of society and are very difficult to avoid without knowing the law. One type of buying and selling transaction that is often practiced is buying and selling sengon wood using a delayed logging system. In this transaction, it appears that one of the parties suffered a loss due to the delay in logging, but this was carried out voluntarily. In this case, the researcher examines the practice of these transactions from the perspective of Islamic law in order to provide legal certainty.